Digital-Based Sustainable Gastronomic Heritage Educational Tourism in Cibuluh Village, Subang Regency, West Java Province - Turgarini, Dewi; Setyorini, Heri; Kusumah, Ahmad Galih Hudaiby; Ningsih, Caria; Gitasiswara, .; Rahmasari, Annisa Aulia; Wiriadi, Reyfan Triansyah (Gastronomy Tourism Journal, 2025)
Cibuluh Village in Subang Regency in West Java Province is a leading village in West Java because of its cultural wealth and natural tourism, but cultural tourism based on sustainable gastronomy approach studies has not been carried out. Researchers are trying to do community service to develop special interest educational tourism to integrate the use of digital technology for education, cultural preservation, and gastronomy simultaneously. As well as researching the sustainability of economic and cultural aspects through a digital tourism model in Cibuluh Village in particular. The analysis uses the theory of cultural heritage, gastronomy components, educational tourism, sustainable tourism development, tourist interest, digitalization, community participation. The results of the study are that Cibuluh Village has great potential in local gastronomic cultural heritage that is distinctive and authentic, both in terms of local food ingredients, traditional processing techniques, and cultural values contained in its culinary practices. Then the Cibuluh Village Community showed enthusiasm and initial readiness to participate in the development of gastronomic educational tourism, although capacity building is still needed in the aspects of education, hospitality, and digitalization. Digitalization is a key factor in expanding the reach of village gastronomy tourism promotion and marketing. However, the limitations of digital literacy and ICT infrastructure are currently challenges that must be overcome through ongoing training and technical support. There are potential tourists (especially from big cities) showing high interest in local culinary interaction and education-based tourism experiences, with a preference for authentic, sustainable experiences that have not been touched by mass tourism. The development of gastronomic educational tourism in Cibuluh Village must be based on the principle of sustainability, namely by actively involving local communities, maintaining cultural authenticity, and utilizing technology wisely to support conservation and promotion. Therefore, multi-party synergy is needed between village communities, local governments, universities, creative industry players, and digital platforms to ensure that this initiative not only has an economic impact, but also socially, culturally, and ecologically in the long term.